2020
DOI: 10.1093/ee/nvaa033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Plant Resistance to Arthropod Pests

Abstract: Temperature has a strong influence on the development, survival, and fecundity of herbivorous arthropods, and it plays a key role in regulating the growth and development of their host plants. In addition, temperature affects the production of plant secondary chemicals as well as structural characteristics used for defense against herbivores. Thus, temperature has potentially important implications for host plant resistance. Because temperature directly impacts arthropod pests, both positively and negatively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…2 C). The corresponding findings confirmed that temperature positively influenced plants by accelerating growth rate, increasing size, implicating host resistance to pests, and improving soil nutrients 72 , 73 . On the other hand, the highly and moderately suitable area of F. delavayi was reduced by 1% under the high emission (SSP585) scenario, with respect to those in the current situation (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 57%
“…2 C). The corresponding findings confirmed that temperature positively influenced plants by accelerating growth rate, increasing size, implicating host resistance to pests, and improving soil nutrients 72 , 73 . On the other hand, the highly and moderately suitable area of F. delavayi was reduced by 1% under the high emission (SSP585) scenario, with respect to those in the current situation (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Building on previous work demonstrating significant indirect effects of temperature on plant resistance and herbivore performance (Bauerfeind & Fischer, 2013; Hamann et al, 2021; Kharouba & Yang, 2021; Nechols et al, 2020), as well as effects of experimental warming on interactions of high‐elevation plant communities with herbivores (Birkemoe et al, 2016; Descombes, Kergunteuil, et al, 2020; Descombes, Pitteloud, et al, 2020), the current findings demonstrate that the response of plant populations to warming can vary across broad environmental gradients, with implications for their interactions with herbivores. Growing A. alpina under warm conditions resulted in reduced performance of herbivores, consistent with the warming‐induced resistance seen in other low‐elevation Brassicaceae (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Building on previous work demonstrating significant indirect effects of temperature on plant resistance and herbivore performance (Bauerfeind & Fischer, 2013;Hamann et al, 2021;Kharouba & Yang, 2021;Nechols et al, 2020), as well as effects TA B L E 3 Statistical significance of the fixed effects of elevation (or population), temperature and relevant covariates on (a) larval performance, and (b) morphological traits (trichome density and SLA) following model simplification. For both (a) and (b) separate models were used to test the interaction between elevation and temperature (upper rows), and population and temperature (lower rows).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations